Extracting functionally feedforward networks from a population of spiking neurons - Vincent, Kathleen; Tauskela, Joe; Thivierge, Jean-Philippe (Frontiers in Computational Neuroscience, 2012)
Neuronal avalanches are a ubiquitous form of activity characterized by spontaneous bursts whose statistics follow a power-law. Recent theoretical models capture neuronal avalanches by assuming the presence of functionally feedforward connections (FFCs), whereby avalanches are generated by a feedforward chain of activation that persists despite being embedded in a massively recurrent circuit. However, it is unclear to what extent networks of living neurons that exhibit neuronal avalanches rely on FFCs. Here, we employed a computational approach to reconstruct the functional connectivity of cultured cortical neurons plated on multielectrode arrays and investigated whether drug-induced alterations in avalanche dynamics are accompanied by changes in FFCs. We begin by extracting a functional network of directed links between pairs of neurons, and then evaluate the strength of FFCs using Schur decomposition. In a first step, we show that, in simulations of spiking neurons, the strength of FFCs is monotonically related to the proportion of feedforward propagation. Next, we estimated the FFCs of spontaneously active cortical cultures in the presence of either a control medium, a GABAA receptor antagonist (PTX), or an AMPA receptor antagonist combined with NMDA receptor antagonist (APV/DNQX). Avalanche sizes in these cultures followed a shallower power-law under PTX (due to the prominence of larger avalanches) and a steeper power-law under APV/DNQX (due to avalanches recruiting fewer neurons) relative to control cultures. The strength of FFCs increased following application of PTX, consistent with an amplification of feedforward activity during avalanches. Conversely, FFCs decreased after application of APV/DNQX, consistent with fading feedforward activation. The observed alterations in FFCs provide experimental support for recent theoretical work linking power-law avalanches to the feedforward organization of functional connections in local neuronal circuits.